Elemen Yang Mempengaruhi Minat Mahasiswa Akuntansi dalam Pemilihan Karir Sebagai Akuntan Publik: Moderasi Financial Reward - Aprilia Sari, Petty (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To determine the factors that influence the interest of accounting students at STIE Putra Perdana Indonesia in choosing a career as a public accountant by testing several variables that influence it. Background Problems: Accounting students at STIE PPI consider that a person works not only to meet economic needs, but there are other reasons that underlie why someone works. Novelty: Retesting the same variables by previous researchers by adding moderating variables. Research Methods: This study uses a quantitative descriptive method, using primary data conducted by distributing questionnaires. The subjects of this study were accounting students of the 2019 intake. Findings/Results: Job market considerations have a significant effect on accounting students' interest in choosing a career as a public accountant. Professional training and professional recognition do not have a significant effect on accounting students' interest in choosing a career as a public accountant. Financial rewards are unable to moderate the influence of job market considerations, professional training and professional recognition on accounting students' interest in choosing a career as a public accountant. Conclusion: Can provide an overview of the profession as an accountant, both public accountants and non-public accountants. So that students have an overview of the profession they will choose.